Acceptance of Game-Based Learning and Intrinsic Motivation as Predictors for Learning Success and Flow Experience - Manuel Ninaus; Korbinian Moeller; Jake McMullen; Kristian Kiili (Serious Games Society, 2017)
There is accumulating evidence that engagement with digital math games can improve students' learning. However, in what way individual variables critical to game-based learning influence students' learning success still needs to be explored. Therefore, the aim of this study was to investigate the influence of students' acceptance of game-based learning (e.g., perceived usefulness of a game as a learning tool, perceived ease of use), as well as their intrinsic motivation for math (e.g., their math interest, self-efficacy) and quality of playing experience on learning success in a game-based rational number training. Additionally, we investigated the influence of the former variables on quality of playing experience (operationalized as perceived flow). Results indicated that the game-based training was effective. Moreover, students' learning success and their quality of playing experience were predicted by measures of acceptance of game-based learning and intrinsic motivation for math. These findings indicated that learning success in game-based learning approaches are driven by students' acceptance of the game as a learning tool and content-specific intrinsic motivation. Therefore, the present work is of particular interest to researchers, developers, and practitioners working with game-based learning environments.